2014
DOI: 10.1371/journal.ppat.1004205
|View full text |Cite
|
Sign up to set email alerts
|

A Central Role for Carbon-Overflow Pathways in the Modulation of Bacterial Cell Death

Abstract: Similar to developmental programs in eukaryotes, the death of a subpopulation of cells is thought to benefit bacterial biofilm development. However mechanisms that mediate a tight control over cell death are not clearly understood at the population level. Here we reveal that CidR dependent pyruvate oxidase (CidC) and α-acetolactate synthase/decarboxylase (AlsSD) overflow metabolic pathways, which are active during staphylococcal biofilm development, modulate cell death to achieve optimal biofilm biomass. Where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
147
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(164 citation statements)
references
References 46 publications
15
147
0
Order By: Relevance
“…8C), longer than the doubling time exhibited by the wildtype strain. Previous studies showed that glucose stimulates MRSA cell death (65) and biofilm formation (12,66).…”
Section: Discussionmentioning
confidence: 97%
“…8C), longer than the doubling time exhibited by the wildtype strain. Previous studies showed that glucose stimulates MRSA cell death (65) and biofilm formation (12,66).…”
Section: Discussionmentioning
confidence: 97%
“…S1A in the supplemental material). This is most likely due to the inability of acetate (pK a ϭ 4.8) to permeate cells and acidify the cytoplasm under relatively neutral conditions (13). Much to our surprise, however, measurements of acetate production and culture pH revealed that the ⌬srrAB mutant produced nearly identical amounts of acetate compared to that of the wild-type strain (Fig.…”
Section: Disruption Of Srrab Enhances Weak Acid-dependent Deathmentioning
confidence: 89%
“…Flow cytometry was performed as previously described (13). Briefly, a BD LSR II flow cytometer (Becton and Dickinson, San Jose, CA) was used to perform analyses using 1-and 3-day-old stationary-phase cultures of S. aureus.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations